2020
DOI: 10.3390/jmse8020074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Verification of Reliability Assessment Techniques for Fuel Cell-Based Hybrid Power System for Ships

Abstract: In order to secure the safe operation of the ship, it is crucial to closely examine the suitability from the design stage of the ship, and to set up a preliminary review and countermeasures for failures and defects that may occur during the construction process. In shipyards, the failure mode and effects analysis (FMEA) evaluation method using risk priority number (RPN) is used in the shipbuilding process. In the case of the conventional RPN method, evaluation items and criteria are ambiguous, and subjective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In the case of FMEA, the estimation is based on the aggregation of three rating factor values (probability of occurrence, severity of consequences, and degree of undetectability). The most typical aggregation of these values is multiplication, as many scientific papers refer to it [1,2,[18][19][20].…”
Section: Brief Description Of the Rm And Fmeamentioning
confidence: 99%
“…In the case of FMEA, the estimation is based on the aggregation of three rating factor values (probability of occurrence, severity of consequences, and degree of undetectability). The most typical aggregation of these values is multiplication, as many scientific papers refer to it [1,2,[18][19][20].…”
Section: Brief Description Of the Rm And Fmeamentioning
confidence: 99%
“…Despite this, there have been only a few studies focusing on the utilization of H 2 -powered fuel cells for passenger ships [22,23]. Additionally, only a small number of demonstration boats [23][24][25] featuring proton-exchange membrane fuel cells (PEMs) with installed power capacities of up to 100 kW have been successfully tested for propulsion in both inland waters and the open sea. A literature review of existing studies on FCs for maritime applications revealed several key considerations: weight and volume, unit costs [26], safety and reliability analysis [27], and integration into hybrid systems for efficient solutions [25,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A failure mode and effects analysis (FMEA) approach was proposed to evaluate the safety and reliability of a hybrid MCFC-GT system for LH 2 tankers [24]. A similar approach was verified by successfully applying it to a hybrid power system composed of a MCFC, a battery system and a diesel engine [25].…”
Section: Introductionmentioning
confidence: 99%